Monograph on neem (Azadirachta indica A. juss.) - Tewari, D. N. (Dina Nath), 1937- (Dehra Dun, India : International Book Distributors, 1992)
On the theoretical and applied perspectives of the Margosa (Neem tree) in India.
Includes indexes.
"Bibliography on Neem": p. 193-247.
Includes bibliographical references.
Keywords: Neem; Neem products; Neem -- India